From Adequacy and Support to Disappointment and Confi rmation of Election Results: Political Refl ection on the Spanish “Dependency Law”. - Lavie, Alfredo Hidalgo (Studia Europaea Gnesnensia, 2011)
The Spanish act of 2006, on supporting personal autonomy and respect for persons and families in the situation of dependency, better known as the “Dependency Law”, was pronounced by many sectors in Spain as a milestone in the history of social ben-efits. Indeed, for the first time, the act recognizes these services and benefits which had hitherto been classified as citizen rights to be subjective rights. Yet already two years after its passing, both among the society as well as among the specialists a frustration had grown. Due to the fact that the provisions of the act had not been put into practice, for which the autonomous governments responsible for its implementation also bear responsibility, the illusion which accompanied its passing is being dispelled.